PENYULUHAN PENGELOLAAN DESA WISATA DI DESA WISATA BELUMBANG TABANAN BALI - I Made Bayu Wisnawa; I Gusti Ayu Mahanavami (Universitas Triatma Mulya, 2023)
Tourism is a major driver of prosperity in Indonesia, but the COVID-19 pandemic has posed challenges to the sector. Bali is a popular tourist destination that has been designated as a tourism village. This designation brings opportunities and challenges, including the need to address human resource challenges. Academics can play a pivotal role in advancing human resources in the tourism sector by educating and training future tourism professionals. They can also conduct research and innovation to enhance service quality and sustainability in tourism. This community engagement program disseminated knowledge about tourism management in Belumbang Village. The results showed that participants' understanding of various aspects of tourism significantly improved.The successful outcome of the engagement program can be attributed to meticulous planning, active participant involvement, adequate resources, leadership support, and a conducive community environment. The active role of the village chief in endorsing and motivating the community's participation also played a crucial role.Continuous training and awareness-raising initiatives are essential for community-based tourism development. Further actions can include advanced training, effective marketing strategies, and sustained commitment to manage Belumbang Village's tourism sustainably.Community-based tourism holds immense potential for revitalizing Bali's tourism sector. The active engagement of academics, combined with community involvement, creates a robust foundation for sustainable tourism development.